2003
DOI: 10.1002/ardp.200390005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 5‐Substituted 2‐Methylbenzimidazoles with Anticancer Activity

Abstract: A series of compounds comprising the thiocarboximidopyrazolyl 5, the phenylpyrazolyl 6, the dimethylpyrazolyl 7, the nitrophenylpyrazolyl 8, the dimethyloxazolyl 9, the benzoxazepinyl 10, and pyrimidyl 11 a-c derivatives of 3-(2-methyl-1H-benzimidazol-5-ylazo)pentane-2, 4-dione was synthesized. Moreover, 5-amino-2-methylbenzimidazole (3) was reacted with phthalic anhydride or maleic anhydride in acetic acid or in toluene to produce 12-15. Treating 5, 6-diamino-2-methylbenzimidazole (16) with ethyl cyanoacetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 12 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Chemistry 2-Methyl-5-nitro-1H-benzimidazole 1, previously described by our group 17,18,20,41 , was used as a starting material to prepare benzimidazole derivatives. During transformation of compound 1 into 2, alkylation occurred using allyl bromide with stirring at room temperature in DMF and sodium hydride.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemistry 2-Methyl-5-nitro-1H-benzimidazole 1, previously described by our group 17,18,20,41 , was used as a starting material to prepare benzimidazole derivatives. During transformation of compound 1 into 2, alkylation occurred using allyl bromide with stirring at room temperature in DMF and sodium hydride.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that thiadiazole ring linked at position 1 to benzimidazole ring through a methylene group, I, has cytotoxicity against breast cancer (MCF-7; Figure 1) 17 . The 1-substituted-2-methyl benzimidazole derivative II was reported to be cytotoxic against non-small lung cancer and breast cancer 18 . It was evident that 1-(4-bromobenzyl) benzimidazole derivative III was the most potent androgen receptor antagonist for prostate cancer 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 96 and 97 possessed significant inhibitory activities against Burkitt's lymphoma promotion . Compounds 98 , 99 (log GI 50 = 5.61), and 100 had high cytotoxic activities against non‐small lung cancer while their result on breast cancer were 98 (log GI 50 = 5.77) and 99 (log GI 50 = 5.36) . Other benzimidazole templates with strong in vitro antitumor activities against various cancer cell lines include 101 – 105 (Fig.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Benzimidazole derivatives are compounds that have received much attention because of their applications in several areas. They are used as antibacterial (Ö zden et al, 2004), anticancer (Easmon et al, 2001;Zhu et al, 1999), anti-inflammatory (Tewari & Mishra, 2001) and antiulcer agents (Shafik et al, 2004;El-Naem et al, 2003). They also have herbicidal, insecticidal and complexing properties (Sbai et al, 2003(Sbai et al, , 2002Attar et al, 2001).…”
Section: Commentmentioning
confidence: 99%